Investing for growth : how to make money by only buying the best companies in the world, an anthology of investment writing, 2010-20 - Smith, Terry, 1953- (Petersfield, Hampshire, Great Britian : Harriman House, 2020)
Leading fund manager Terry Smith debunks the many myths of investing - and making the case for simply buying the best companies in the world. With his trademark razor-sharp wit, Smith not only reveals what these high-quality companies really look like and where to find them, but also why you should avoid companies that abuse the English language, how most share buybacks actually destroy value and how ESG investors often end up with investments that are far from green or ethical. He also reveals ten golden rules for invvestment.
Foreword / Lionel Barber -- The lessons of the first ten years / Terry Smith -- Fund management fees -- Annual letter to shareholders 2010 -- Share buybacks - friend or foe? -- Exchange-traded funds are worse than I thought -- Accelerated stock repurchases -- Murdoch should give up control of News Corp -- News Corp: a family business -- UBS debacle highlights dangers of ETFs -- The great contender -- how Smokin' Joe Frazier defined an era -- Annual letter to shareholders 2011 -- Traders are the ruin of retail banking -- Lessons of the great Wall Street Crash -- Lessons from the Tour de France -- Annual letter to shareholders 2012 -- Return-free risk -- why boring is best -- Ten golden rules of investment -- Market timing: don't try this at home -- Sorting the wheat from the chaff -- Never invest just to avoid tax -- Too many stocks spoil the portfolio -- Keep a lid on costs to protect yourinvestment -- If they use these words, don't buy their shares -- Why it is safe to pay up for quality -- It's deja vu all over again -- Annual letter to shareholders -- Just the facts when weighing investments -- Shale: miracle, revolution or bandwagon? -- Investors are their own worst enemies -- Big Blue investors may not have a winning hand -- What did you invest in before the war,great-grandpa? -- Why buy Brics when you can have Mugs? -- A hitchhiker's guide to emerging markets -- How investors ignored the warning signs at Tesco -- Eureka! I discovered how funds are named -- Why I don't own bank shares -- Is this the next Tesco? -- Let's all do the corporate hokey-cokey -- Annual letter to shareholders 2014 -- What exactly do we mean by "shareholder value"? -- Shareholder value is an outcome, not an objective -- Three steps to heaven -- Where's the beef? McDonald's uncertain recovery -- What investors can learn from Alex Bird's 500 winning bets at the races -- What investors can learn from Sir Alex Ferguson's success -- Bond proxies: can you afford not to own them? -- Income is not what it used to be -- Keep your eyes on the prize: total return is what matters -- Why bother cooking the books if no one reads them? -- Firms which provide good products or services are key to investing -- What I have learnt at Fundsmith in the past five years -- Annual letter to shareholders 2015 -- If you do one thing with your money in 2016 179 Financial Times, 15 January 2016 -- Investors should not write off bond proxies -- What the Nifty Fifty can tell us about bond 184 (3)proxies -- Stay focused on the `known knowns' -- Annual letter to shareholders 2016 -- Emerging markets ETFs and the Jaws of Death -- The unique advantage of equity investment -- AstraZeneca is beginning to look like Tesco -- Annual letter to shareholders 2017 -- ESG? SRI? Is your green portfolio really green? -- Adding small-caps to a global equity -- portfolio adds value without heightening the risk -- Who needs income? -- Do equities outperform bonds? -- Annual letter to shareholders 2018 -- The myths of fund management -- Annual letter to shareholders 2019 -- A pandemic letter to shareholders -- Never let a crisis go to waste -- There are only two types of investors -- In order to finish first -- Index.
Includes index.
Keywords: Investments; Stocks; Investment analysis